Фемiнативи украïнськоï мови: проблема лексикографiчноï об’єктивацiï стилiстичноï характеристики «розм.» - Arkhangel’s’ka, Alla (Wiener Slawistischer Almanach, 2023)
The study deals with the lexicographic objectification of functional and stylistic characteristics of Ukrainian female nominations, in particular those marked as “colloquial”, in monolingual dictionaries of the Ukrainian language and bilingual lexicographic works from the second half of the twentieth and the beginning from the twenty-first centuries. Consideration is given to an understanding of the marker “colloquial” in the theory and practice of Ukrainian lexicography; dynamics and content in interaction with adjacent functional-stylistic markers are also traced. Numerous inconsistencies were found both in the inclusion/non-inclusion of female nominations in the dictionaries and in marking them as colloquial units of the Ukrainian lexicon. Such phenomena reflect, on the one hand, real world linguistic dynamics. On the other hand, they also illustrate the subjective complexity of the lexicographic representation of such nominations in view of the expressive specificity of these units and their stylistic status.